Revisiting the scope and expectations of implementation science and implementation science communications - Wilson, Paul; Aarons, Gregory A.; Sales, Anne; Xu, Dong (Roman); Wensing, Michel; Hutchinson, Alison; Beidas, Rinad S.; Geng, Elvin (Implementation science, 2024)
This editorial updates the scope and submission expectations of Implementation Science and Implementation Science Communications. We refine our protocol publishing policies and set out new expectations for reporting studies describing determinants and their relationship with implementation outcomes. Our central focus remains on the implementation of evidence-based interventions into healthcare practice and policy. We are most interested in rigorous empirical studies of the implementation of evidence-based healthcare interventions, practices, and policies, and the de-implementation of those that are demonstrated to be of low-value or no benefit. Alongside this, we remain interested in the systematic study of implementation mechanisms and processes and on the influences of patient, professional, and organizational behaviours. Novel theoretical and methodological developments are considered. For all submissions, we expect authors to demonstrate how their work is integrated with existing knowledge in the field and to clearly state the added value of the work to the field broadly.